The Welfare versus Work Paradox - Roberto Iacono (PLoS ONE, 2025)
How can countries balance work incentives and access to welfare without violating the principle that work shall always be strictly preferred to welfare? In a context in which wages stagnate or drop, and benefit levels are reduced due to austerity measures, the welfare versus work paradox arises. This research shows analytically that when both wages and benefits approach the subsistence level, welfare becomes preferable to work, violating the work incentive principle. The policy implication of this result is that, to maintain the validity of the work incentive principle, minimum wages must be kept above the subsistence threshold.